Analisis Kebutuhan Pelatihan di Desa Wisata Darubia, Kabupaten Bulukumba - Zulkifli, Andi; Jaya, Risman; Ismail (Jurnal Abdimas Pariwisata, 2025)
Analysis of Training Needs in Darubia Tourist Village, Bulukumba Regency. Darubia Tourism Village in Bulukumba Regency, South Sulawesi, has great tourism potential with its natural beauty and rich local culture. However, challenges such as inadequate infrastructure and low awareness of the importance of cleanliness pose obstacles to developing tourism in this village. This report documents community service activities aimed at improving the cleanliness management of homestays and diversifying creative economy products. Through surveys and interviews with the local community, a need for training in homestay cleanliness management, hygiene and sanitation, and local product development was identified. The designed training program includes technical guidance on hygiene standards, sanitation management, and enhancing creativity in craft products. The results of this activity are expected to improve the quality of homestay services and the competitiveness of local products, which in turn will support the sustainable development of tourism in Darubia Village.